Efficiency of low-temperature adsorptive hydrogen storage systems - Adametz, Patrick; Müller, Karsten; Arlt, Wolfgang (International Journal of Hydrogen Energy, 2014)
This study presents a thermodynamic analysis of adsorptive hydrogen storage systems at cryogenic temperatures, focusing mainly on the efficiency of the storage system. Four different operation modes, differing in the process used to release the hydrogen and the availability of cooling during storage time, are examined. A sensitivity analysis was performed to determine the dependency of the efficiency on several input parameters including storage time, enthalpy of adsorption, energy required for cooling, and system size. It can be concluded that the energetic efficiency of the hydrogen storage system not considering production and usage steps ranges from 65 to 81% for short storage times, depending on the energy effort and hydrogen losses of the applied operation mode. The storage time has the most noticeable impact on efficiency and cryo-adsorptive hydrogen storage is not suitable for long storage times due to the increasing cooling effort or hydrogen losses. For short storage times e.g. hours, cooling during storage time may be omitted due to the low hydrogen losses. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Energy storage; Hydrogen; Adsorption; Efficiency; Storage density; Thermodynamic analysis

Efficient hydrogen storage: LOHC vs. other technologies - Arlt, Wolfgang; Adametz, Patrick; Müller, Karsten (Sustainable Engineering Forum 2014 - Core Programming Area at the 2014 AIChE Annual Meeting, 2014)

Energetic evaluation of hydrogen storage in metal hydrides - Adametz, Patrick; Müller, Karsten; Arlt, Wolfgang (International Journal of Energy Research, 2016)

Potential analysis for the improvement of chemical energy transformation processes - Adametz, Patrick; Baumgärtner, Andrea; Kohler, Tobias; Obermeier, Jonas; Siebert, Daniel; Müller, Karsten (Chemical Engineering & Technology, 2017)
Much research aims to improve the efficiency of energy processes. However, it is often not clear where the biggest potential for improvement lies. Crucial for a namable improvement is a realistic chance for advancing the respective element as well as a significant influence of the respective element on the overall performance. A study on the potential for improving the efficiency of five exemplary chemical-energy systems is presented. It was found that replacing working substances by alternatives with better enthalpies of reactions or solubility behavior carries huge potential for improving energy processes. However, in most cases there is little potential, for example, in lower heat capacity, even though heat capacity highly influences the efficiency of the processes.

Thermodynamic analysis of hydrogen storage in metal hydrides - Adametz, Patrick; Müller, Karsten; Arlt, Wolfgang (Sustainable Engineering Forum 2014 - Core Programming Area at the 2014 AIChE Annual Meeting, 2014)

Thermodynamic evaluation and carbon footprint analysis of the application of hydrogen-based energy storage systems in residential buildings - Adametz, Patrick; Pötzinger, Christian; Müller, Stefan; Müller, Karsten; Preißinger, Markus; Lechner, Raphael; Brüggemann, Dieter; Brautsch, Markus; Arlt, Wolfgang (Energy Technology, 2016)